miRNA-150_R-1 mediates the HIF-1/ErbB signaling pathway to regulate the adhesion of endometrial epithelial cells in cows experiencing retained placenta - Lv, Chen; Li, Zongshuai; Wang, Qi; Wang, Yue; Zhao, Xingxu; Zhang, Yong (Frontiers in Veterinary Science, 2022)
Retained placenta (RP) refers to reproductive disorders caused by the failure of fetal membranes to be expelled 12 h after delivery in dairy cows. Postpartum adhesion of the fetal membranes to the uterus causes diseases such as mastitis or endometritis, which threatening the profitability of the dairy industry. Emerging evidence suggests that micro RNAs (miRNAs) play crucial roles in various processes, such as the occurrence and progression of fetal membranes discharge. However, the molecular mechanisms of miRNAs in RP remain unknown. In this study, we performed RNA-sequencing to characterize the expression profiles of mRNAs and miRNAs in caudal vein blood samples of postpartum Holstein cows whose fetal membranes were discharged normally or retained to identify RP-related genes and evaluate their molecular mechanisms. We identified 44 differentially expressed miRNAs (19 upregulated and 25 downregulated) and 706 differentially expressed mRNAs (325 upregulated and 381 downregulated) in the RP group compared to the normal fetal membranes discharge group. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis revealed that differentially expressed mRNAs were mainly enriched in the extracellular matrix, cell adhesion, and autoimmunity-related biological processes or pathways. Further analyses using RNA-sequencing, a dual luciferase reporter system, quantitative reverse transcription-PCR, immunofluorescence, and western blotting verified that endothelial PAS domain protein 1 (EPAS1) is regulated by miR-150_R-1 in endometrial epithelial cells. We demonstrated the relationship between EPAS1 and RP and confirmed that EPAS1 is upregulated in the blood and placenta of cows that experience RP. Further, we proposed a model of the miRNA-mRNA negative regulatory network mediated by the HIF-1/ErbB signaling pathway to show its regulatory role in RP.